1991
DOI: 10.1515/zna-1991-1-206
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Potential Function for Hydroxylamine Dimer Interactions from ab initio Calculations

Abstract: Dedicated to Dr. K. Heinzinger on the occasion of his 60 th birthdayThe derivation of an intermolecular potential function for the interaction of two hydroxylamine molecules, based on ab initio SCF-ECP calculations is reported. Ab initio values were compared for selected geometries with those obtained from calculations with much larger basis sets, inluding electron correlation effects by the CEPA method. A total 658 energy values were then fitted to an analytic sum of atom-atom isotropic pair potential functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…For water-water interactions, the CF2 potential [3] has been used, and the potential of Michopoulos, Botschwina and Rode [8] was employed for the evalu ation of hydroxylamine-hydroxylamine pair ener gies. For water-hydroxylamine, our recently con structed potential containing the Coloumb-, r~3-, r~6-, r _9-terms and one exponential term [15], was utilized.…”
Section: Methods 1 Intermolecular Potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…For water-water interactions, the CF2 potential [3] has been used, and the potential of Michopoulos, Botschwina and Rode [8] was employed for the evalu ation of hydroxylamine-hydroxylamine pair ener gies. For water-hydroxylamine, our recently con structed potential containing the Coloumb-, r~3-, r~6-, r _9-terms and one exponential term [15], was utilized.…”
Section: Methods 1 Intermolecular Potentialsmentioning
confidence: 99%
“…Further, all simulations were performed with rigid molecules. The possible errors caused by these simplifications have been inves tigated in previous studies [8,15] and were found to be well tolerable while aiming mainly at structural data.…”
Section: Intermolecular Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous note [4] details were presented of the construction of such a potential function for the intermolecular interactions of hydroxylamine (NH20H) 0 1992 John Wiley & Sons, Inc.…”
Section: Introductionmentioning
confidence: 99%
“…The main difficulties in obtaining a potential function for hydroxylamine dimer interactions originated from the fact that hydroxylamine molecules can form several types of hydrogen-bonded dimers with only minor differences in their stabilization energies. Indeed, accurate quantum mechanical calculations and careful fitting methods were required until a potential function was finally obtained [4]. In this article the potential model is reviewed (Sec.…”
Section: Introductionmentioning
confidence: 99%